Isolation and Identification of Andrographis paniculata (Chuanxinlian) and Its Biologically Active Constituents Inhibited Enterovirus 71-Induced Cell Apoptosis - Chao, Wen-Wan; Kuo, Yueh-Hsiung; Lin, Bi-Fong (Frontiers in Pharmacology, 2021)
Aim: Andrographis paniculata (Burm. f.) Nees. (also known as Chuanxinlian in Chinese) of Acanthaceae family is one of the Chinese herbs reputed to be effective in the treatment of inflammation, infection, cold and fever. Enterovirus 71 (EV71) is one of the most important enterovirus that causes hand-foot and mouth disease (HFMD) accompanied with neurological complication. Methods: To explore an anti-infective Chinese herb medicine, pure compounds isolated or its synthesized analogues from A. paniculata (AP) ethyl acetate (EtOAc) extract are used to explore their anti-EV71 activities. The antiviral activity were determined by cytopathic effect (CPE) reduction and sub-G1 assays for measuring lysis and apoptosis of EV71-infected rhabdomyosarcoma (RD) cells. IFNγ-driven luciferase reporter assay, to evaluate their potential roles in activation of immune responses. Results: Our data showed that EV71-induced sub-G1 phase of rhabdomyosarcoma (RD) cells was dose-dependently increased. Highly apoptotic EV71-infected RD cells were reduced by AP extract treatment. Ergosterol peroxide (4) was the most effective anti-apoptotic effect among these 7 compounds. In addition, the compound 8 synthesized from acetylation of compound 7 showed significantly better antiviral activity, the lowest sub-G1 phrase of 6 18%. Further investigation of IFNγ-inducer activity of these compounds showed that compounds 3, 6, 10, 11 and 12 had significantly higher IFNγ luciferase activities, suggesting their potential to promote IFNγ expression and thus activate immune responses for anti-virus function. Conclusion: Our study demonstrated that bioactive compounds of AP and its derivatives either protecting EV71-infected RD cells from sub-G1 arrest or possessing IFNγ-inducer activity might be feasible for the development of anti-EV71 agents.